Theorien! Horizonte für die Lehrerinnen und Lehrerbildung - Harant, Martin; Thomas, Philipp; Küchler, Uwe (Schriftenreihe der Tübingen School of Education, 2020)
Why do I have to deal with theories, I just want to become a teacher? This is the question asked by student teachers in educational science and didactics. The contributions to the volume 'Theories! Horizons for Teacher Education' offer an answer to this question: On the one hand, our society needs the discussion about the overall orientation of its educational goals and likewise the fruitful dispute within the educational sciences and the reference sciences of the school subjects. In a time of political, social and cultural upheaval in education, the need for orienting reflection comes more to the fore. Theoretical discourses are the place of this self-orientation. Then, student teachers must be enabled to think multi-perspectively. They can learn this best by dealing with theories. The individual contributions of the volume show what theories make visible in a new way and what they close off on the other hand, if they are received in a one-sided or totalizing way. After all, theories have a genuine heuristic power, theories make visible, they open doors, they let us understand something anew. Accordingly, the contributions to this volume ask: Where can we find, whether in educational science or subject didactics, examples of aha experiences or of an understanding of larger contexts that only become possible through theoretical penetration? What do we see in the world, in our lives, and as a phenomenon in a completely new way when we have understood a theory?